The effectiveness of small heterodimer partner and FGF 19 levels in prediction of perinatal morbidity in intrahepatic cholestasis of pregnancy. (4th July 2022) - Bayram, Mehmet; Irak, Kader; Cifci, Sami; Koksal, Ali Riza; Kazezoglu, Cemal; Acar, Zuat; Ozarı, Halil Onur; Alkim, Huseyin
Abstract: Fibroblast growth factor 19 (FGF19) and small heterodimer partner (SHP) are molecules responsible for controlling serum bile acid levels. We designed this study for evaluating the effects of FGF 19 and SHP in intrahepatic cholestasis of pregnancy (ICP). Fifty-six pregnant women having ICP and 20 healthy pregnant women were included in the study. The patients were followed up until delivery in terms of pregnancy-related morbidity/mortality. Serum FGF 19 and SHP levels were determined by enzyme-linked immunosorbent assay (ELISA). Serum FGF 19 and SHP levels were significantly higher in the patient group compared to the control group ( p : .04, p : .003, respectively). In ROC analysis, SHP level above 1995 ng/L was found effective in predicting the need for neonatal intensive care unit (ICU) follow-up with 53.8% sensitivity and 77.8% specificity. High SHP levels were correlated with perinatal morbidity, mortality and neonatal ICU hospitalisation. Impact Statement: What is already known on this subject? Itching, elevated serum transaminase and serum total bile acid (TBA) levels are the most important clinical and biochemical findings of intrahepatic cholestasis of pregnancy (ICP). Fibroblast growth factor 19 (FGF19) and small heterodimer partner (SHP) are molecules – responsible for controlling serum bile acid levels. ICP is associated with preterm labour, asphyxia, foetal distress, stillbirth and preeclampsia. What do the results of this study add? Serum FGF 19 and SHP levels were significantly higher in the patient group compared to the control group. High SHP level was found effective in predicting the need for neonatal intensive care unit and showed a negative correlation with birth week and birth weight. What are the implications of these findings for clinical practice and/or further research? Checking SHP levels can help to predict perinatal mortality and morbidity. Treatments to be developed through the mechanism of action of FGF 19 and SHP can be promising in the treatment of ICP and other cholestatic liver diseases.